Implementasi Program Jaminan Hari Tua Di Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Kota Manado - PITERADJA, ANGGI CHRISYE; PANGKEY, MASJE SILIJA; RARES, JOYCE JACINTA (Sam Ratulangi University, 2017)
ABSTRACT: This research comes from the phenomenon that program implementation of pension plan is still notoptimal in Manado city. The goal of this research is to find out how the program implementation of pension plan inManado city. The kind of method that used on this research is qualitative research with measured indicators which are;the insurance of external condition that faced by institute or the implementing agency will not causing major problem,whether for implement to provide adequate resources including source of time, whether the necessary integration ofresources are exists, whether the policy that will implemented based on a reliable causal relationship, how many ofcausal relation becomes, whether minor relationship of interdependence, in deep comprehension and agreement ongoals, that tasks have been detailed and placed in the correct order, perfect communication and coordinate, those withpower of authority can demand and achieve perfect obedience. Informant researcher are 10 people. Technique ofcollecting data are used observation, interview and document technique. While the technical analysis used interactivemodel analysis from Miles and Huberman. based on data analysis development, drawn the conclusion that the lack ofhuman resources to provide maximum service to the participants claim, which lack of socialization implemented, in itsimplementation this program is not able to achieve the goals for ensure the workers in old age, causing by new regulationthat manage the implementation of JHT program. Good communication between peer employees has been consist. Also,good cooperation with related agencies is occurred. With assigning tasks on each employer has been set according theirposition. The recommendation that human source possessed to be further enhanced. Socialization is endeavouredthoroughly to all levels of society working both formal and informal sectors to be further improved. it is concern toreview the rules of government that organize about the implementation of old age program.Keywords : Implementation, Of Old Age Program, BPJS Ketenagakerjaan